Effects of physiotherapy in the management of cancer-related pain and fatigue: A systematic review of randomized controlled trials. - Ameer Shaikh, Hajra; Anjum, Okasha; Iqbal , Kiran; Zaidi, Syeda Wajeeha Raza (International Journal of Endorsing Health Science Research, 2021)
Background: Cancer is ranked as the 2nd common deadliest disorder worldwide, and the growing incidence demands updating and optimizing the treatment strategies for cancer survivors. However, evidence regarding this area is scarce; therefore, this systematic review aimed to evaluate the effects of Physiotherapy (PT) in managing cancer-related pain and fatigue. Methodology: Electronic search conducted utilizing Google Scholar, Embase.com, Cochrane CENTRAL via Wiley, Web of Science Core Collection, MEDLINE via Ovid, PEDro, and PubMed. Randomized controlled trials published from 2014 to April 2021 analyzing the effects of PT approaches for cancer-related pain and/or fatigue management in adult cancer patients were included in the review. Sixteen eligible trials were evaluated, of which eight trials addressed Cancer-Related Pain (CRP) while others addressed Cancer-Related Fatigue (CRF). The risks of bias and trials credibility were analyzed via the Cochrane tool to assess bias risk. Results: Strong evidence favors the effectiveness of various PT approaches mainly, aerobic and resistance exercises for CRF and CRP management. However, endurance exercises, high-intensity interval training, and myofascial release were effective in CRF management. In contrast, Xbox Kinect-based games, stretching, lymphatic drainage, and passive mobilization effectively reduced CRF. Conclusion: Large body of evidence supports the effectiveness of PT exercises mainly, aerobic and resistance exercises, in cancer-associated pain and fatigue management. Hence exercises prescriptions should be implemented in the treatment plan of cancer patients.